Return on Asset, Return on Equity, Gross Profit Margin and Net Profit Margin of manufacturing companies in the Consumer Sector Listed on the Indonesia Stock Exchange and its Impact on Earnings Growth from 2015 to 2022 - Noor Khalifah, Widian; Merliana, Vina (Masyarakat Ekonomi Syariah Bogor, 2024)
With regard to manufacturing businesses in the consumption sector listed on the Indonesia Stock Exchange between 2015 and 2022, the purpose of this study is to ascertain the impact of profitability measures, which include Return on Equity, Gross Profit Margin, and Net Profit Margin, on Profit Growth. An approach to verification and description is combined with a quantitative methodology in this study. A variety of statistical techniques are employed in the testing process, including the partial and simultaneous hypothesis testing (f and t tests), multiple linear regression, Pearson product moment correlation coefficient, determination coefficient, and classical assumption test. For this investigation, the sample was calculated using a combination of nonprobability and purposeful sampling methods. The consumption subsector's 48 manufacturing enterprises' financial reports provide the sample data. The data processing software utilized is SPSS version 26.0. Partially and concurrently, the study's findings indicate that profit growth is unaffected by return on equity, return on assets, gross profit margin, and net profit margin